1981
DOI: 10.1017/s0022112081002966
|View full text |Cite
|
Sign up to set email alerts
|

A visual study of turbulent spots

Abstract: From the results of a flow visualization experiment, certain physical characteristics of a turbulent spot are suggested by the authors. The spot was artificially initiated at a point by a small intermittent wall jet. The authors also carried out experiments behind vibrating trip wires and observed the ‘signatures’ or ‘footprints’ of the A-shaped vortices seen by other workers. The fact that these ‘signatures’ are also observed in a turbulent spot leads one to suspect that these spots consist essentially of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
84
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(97 citation statements)
references
References 9 publications
12
84
0
1
Order By: Relevance
“…We note that the observations made by Carstensen, Sumer, and Fredsøe 1 were actually analogous to those made for steady boundary layers (e.g. Gad-el-Hak, Blackwelder, and Riley; 4 Perry, Lim, and Teh; 5 Chambers and Thomas; 6 Browand and Plocher; 7 Seifert and Wygnanski; 8 and Matsubara and Alfredsson 9 ).…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…We note that the observations made by Carstensen, Sumer, and Fredsøe 1 were actually analogous to those made for steady boundary layers (e.g. Gad-el-Hak, Blackwelder, and Riley; 4 Perry, Lim, and Teh; 5 Chambers and Thomas; 6 Browand and Plocher; 7 Seifert and Wygnanski; 8 and Matsubara and Alfredsson 9 ).…”
Section: Introductionsupporting
confidence: 75%
“…The results of this study confirmed the experimental findings of Carstensen, Sumer, and Fredsøe. 1 In the numerical simulations the turbulent spots appeared at about the end of the accelerating phases at the Reynolds numbers investigated (Re = 3.0 × 10 5 and Re = 4.5 × 10 5 ) and caused spikes in the wall shear stress and the velocity fields. Previously, direct numerical simulations (see, for example, Akhavan, Kamm, and Shapiro; 11 Vittori and Verzicco; 12 and Costamagna, Vittori, and Blondeaux 13 ) have also successfully been utilised to capture transition to turbulence over hydraulic smooth beds, in the form of spikes in the wall shear stress signal (or in the near wall velocity signal) prior to the near wall flow reversal in oscillatory boundary-layer flows, in line with experimental observations (Hino, Sawamoto, and Takasu; 14 and Jensen, Sumer, and Fredsøe 15 ).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Hairpin structures can be seen near the leading edge of the spot, reminiscent of the conceptual picture of Perry et al 23 Quasistreamwise vortices are evident at the lateral extremities of the spot ͑see Sec. V for an explanation of their origin͒.…”
Section: B Structure Of a Spotmentioning
confidence: 62%
“…In their model, an initial disturbance to a laminar boundary layer causes three-dimensional undulations in initially straight vortex bundles aligned in the spanwise direction. Fluctuating velocities induced by the wavy lines of vorticity cause the rapid growth of the turbulent spot in both the spanwise and streamwise directions, resulting in the patterns illustrated in Perry et al (1981). It is probable that there is a direct connection between the observed growth pattern of turbulent spots and the orientation observed in the turbulent boundary layer.…”
Section: Discussionmentioning
confidence: 96%